The Poisson-exponential lifetime distribution - Cancho, Vicente G.; Louzada-Neto, Franscisco; Barriga, Gladys D.C. [UNESP] (Elsevier, 2011)
In this paper we proposed a new two-parameters lifetime distribution with increasing failure rate. The new distribution arises on a latent complementary risk problem base. The properties of the proposed distribution are discussed, including a formal proof of its probability density function and explicit algebraic formulae for its reliability and failure rate functions, quantiles and moments, including the mean and variance. A simple EM-type algorithm for iteratively computing maximum likelihood estimates is presented. The Fisher information matrix is derived analytically in order to obtaining the asymptotic covariance matrix. The methodology is illustrated on a real data set. © 2010 Elsevier B.V. All rights reserved.
Keywords: Complementary risks; EM algorithm; Exponential distribution; Poisson distribution; Survival analysis; Asymptotic covariance matrix; Data sets; EM algorithms; Exponential distributions; Failure rate functions; Formal proofs; Increasing failure rate; Life-time distribution; Maximum likelihood estimate; Algorithms; Bioinformatics; Covariance matrix; Distribution functions; Fisher information matrix; Maximum likelihood estimation; Probability; Probability density function; Risk analysis; Risk assessment